Kebijakan Prioritas Tenaga Kerja Lokal di Kabupaten Bekasi: Analisis Efektivitas, Implikasi Pengkooptasian, dan Strategi Peningkatan Berbasis Meritokrasi - Masnun, Masnun; Hartono, Drajat; Nur Mubin; Fitry, Emly; Sumarno, Sumarno (Jurnal Visi Manajemen, 2025)
This study examines the implementation of the local workforce priority policy in Bekasi Regency during the first six months of the new Regent's leadership (January–June 2025). Although Bekasi is known as a large industrial area with extensive job opportunities, February 2025 data shows that the Open Unemployment Rate (TPT) remains high, at 8.87%, or far above the national average. This condition indicates that the policy based on Regional Regulation (Perda) No. 4 of 2016 has not been running optimally. The analysis results show that the policy implementation faces structural obstacles, one of which is the practice of co-optation in the form of brokering, nepotism, and rent-seeking, which undermine the principle of meritocracy. This situation has resulted in a decline in the quality of human resources recruited by companies and limited opportunities for local job seekers who actually have adequate competence. This report also discusses the legal aspects of the local priority policy, which essentially must be consistent with the principle of non-discrimination and the Supreme Court's decision emphasizing the importance of professionalism in the workplace. Thus, the existence of this policy is not only related to job opportunities, but also concerns the integrity of labor governance. To increase its effectiveness in the future, a comprehensive strategy is needed that includes strengthening regulations to be more adaptive to industry dynamics, increasing transparency and accountability in the recruitment process, developing the capacity of local human resources through targeted training programs, and strict monitoring and law enforcement mechanisms against abuses of authority. Through this integrated effort, it is hoped that the local labor priority policy in Bekasi Regency will not only be a formal instrument but will also be able to have a real impact in reducing unemployment and strengthening the competitiveness of the local workforce amidst the currents of industrial globalization.